Supplementation of Yeast Cell Wall Fraction Tends to Improve Intestinal Health in Adult Dogs Undergoing an Abrupt Diet Transition - Lin, Ching-Yen; Carroll, Meredith Q.; Miller, Michael. J.; Rabot, Rodolphe; Swanson, Kelly S. (Frontiers in Veterinary Science, 2020)
When owners decide to change their pet’s food, a rapid transition may cause gastrointestinal distress. Yeast products may help with digestive upset during diet transition due to the bioactive compounds they possess, which may lead to improved intestinal morphology and integrity, modified gut microbiota, and modulated immune responses. The objective of this study was to determine the effects of a yeast cell wall fraction supplement on measures of gut integrity and fecal characteristics of adult dogs undergoing an abrupt diet transition. Twelve adult female beagles (mean age: 5.16  0.87 years; mean body weight: 13.37  0.68 kg) were used in a replicated 4  4 Latin square design with four 28-day experimental periods. During days 1-14, dogs were fed a dry kibble diet and supplemented with a placebo (cellulose; 125 mg/d) or yeast product (365 mg/d; equivalent to 0.2% of diet). During days 15-28, dogs remained on their placebo or yeast treatments but were rapidly transitioned to a canned diet or high-fiber diet. Fresh fecal samples were collected on days 13, 16, 20, 24, and 27 for measurement of pH, dry matter, calprotectin, immunoglobulin A (IgA), Escherichia coli, and Clostridium perfringens. Blood samples were collected on days 14, 17, and 28 to measure serum lipopolysaccharide-binding protein concentrations. All data were analyzed using the Mixed Models procedure of SAS 9.4. Fecal pH, dry matter, calprotectin, IgA and E. coli were not affected (P > 0.05) by treatment before diet transition. Dogs supplemented with yeast cell wall fraction tended to have higher (P = 0.06) fecal C. perfringens counts than the controls. After diet transition, most parameters were not altered (P > 0.05) by treatment except that yeast-supplemented dogs tended to have higher (P = 0.06) fecal IgA than controls. Our results suggest that the yeast product may modestly improve intestinal health after an abrupt diet transition in adult dogs by enhancing intestinal immunity.